The pattern of state organization in the new constitution of Lithuania: A third way between the presidential and parliamentary systems? - Andreas Hollstein (Politologija)
In this article, Andreas Hollstein refers to the Constitution of the Republic of Lithuania and, by that token, discusses the pattern of state power structure as established by it. The author focuses the analysis upon the following question: does the Constitution of the Republic of Lithuania of 1992 establish a third way between the parliamentary and presidential democracy?